Cognitive Apprenticeship: A Roadmap to Improve Clinical Teaching - Michelle Daniel; Brian Clyne; Rachel Fowler; Elizabeth Sutton; Steven Rougas; Sarita Warrier; Katherine Farmer; Ankur Doshi (Association of American Medical Colleges, 2015)
Abstract The medical profession uses an apprenticeship model to train future generations of physicians. What sets medicine apart from traditional observation-based apprenticeships, however, is the need for clinician educators to externalize their heuristics to make their internal thought processes explicit and visible for a wide range of learners to observe and implement. This form of thinking out loud does not necessarily come naturally to physicians but can be enhanced through training and practice. This resource describes a faculty development workshop to improve the workplace-based teaching skills of physician educators using a cognitive apprenticeship model. Recent studies demonstrate how this theory resonates with actual practice in medical education and highlight areas for improvement in clinical teaching. The model uses six teaching methodologies (modeling, coaching, scaffolding, articulation, reflection, and exploration) situated in a safe learning environment to address clinical instruction across a broad range of learner levels from preclerkship medical students to PGY 1-4 residents training in professional practice. During this highly interactive workshop, physicians discuss case vignettes to identify gaps in common teaching-learning scenarios and work together to develop solutions by applying the cognitive apprenticeship model. This workshop was first developed for emergency medicine physicians. It has since been modified and refined for use as a workshop in several other local, regional, and national education settings. More than 100 faculty have attended the workshop in these varied venues. There was general recognition among participants that the cognitive apprenticeship model was a useful framework for clinical teaching. Evaluations (on a scale from poor to excellent) have been uniformly excellent for quality of handouts, summarizing key points, active learning, and audience participation, and good to excellent for the quality of the background information, clearly presented goals, organization of the activities, and easy to read visuals.